Teas: Direct test on quality and antioxidant activity using electron paramagnetic resonance spectroscopy. Issue 3 (2002) - Morsy Morsy, M. A. M. A.
Abstract : The manufactured teas may conveniently be divided into three classes: Green teas, Oolongs (delicate black teas), and Black Teas. Several indirect methods are employed to measure the antioxidant activity of tea extracts that is basically takes place by monitoring the inhibition of oxidation of a suitable substrate using the extracts of antioxidant materials from the studies systems. This study is concerned with the results of electron paramagnetic resonance (EPR) spectroscopy that is utilized to investigate several categories of green and black teas: Twining Green Tea (TGT) of London, Rabea Green Tea (RGT) of Saudia, Chinese Green Tea (CGT) of China, English Breakfast Tea (EBT) of Ahmed Tea‒London, and Rabea Black Tea (RBT) of Saudia. Three EPR signals from all the studied samples are observed. The assignment of these signals will discussed and correlated with the quality of leaves. Mainly, two paramagnetic species are considered to be responsible for the observed EPR signals; manganese(II)–protein system of the leaves and a stable free radical of aromatic origin. The study will provide facts on the dependency of radical signal on the oxidative degradation procedures of the studied samples. The intensity and feature of Mn(II)‒EPR‒signal is found to be related to the disintegration of tea leaves.